Analisis Kemampuan Berargumentasi Ilmiah Siswa Kelas XI di SMA Negeri 1 Telaga pada Materi Larutan Elektrolit dan Nonelektrolit - Regina Olii; Lukman Abdul Rauf Laliyo; Ahmad Kadir Kilo; Akram La Kilo; Julhim S. Tangio; Erga Kurniawati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to assess the scientific argumentation skills of eleventh grade students at SMA Negeri 1 Telaga on the topic of electrolyte and nonelectrolyte solutions. The study employs a descriptive qualitative approach. The data collection method utilized a multiple-choice test with five indicators of scientific argumentatio, comprising 25 questions. The sample comprises 132 students from the eleventh grade at SMA Negeri 1 Telaga. The results reveal that students’ scientific argumentation skills on the topic of electrolyte and nonelectrolyte solutions are categorized as fair, with a claim level of 48,4%, data level of 53%, warrant level of 50,6%, backing level of 44,4%, and rebuttal level of 44,3%. It can be concluded that while students’ argumentation skills are aduwuate, many students still struggle to present a complete argumentation using all indicators. The active participation of both students and teachers during lessons is crucial to improving students’ scientific argumentation abilities, particularly in overcoming misconceptions related to electrolyte and nonelectrolyte solutions.